Photocatalytic oxidative desulfurization and degradation of organic pollutants under visible light using TiO2 nanoparticles modified with iron and sulphate ions. Issue 5 (1st March 2022) - Ortiz-Bustos, Josefa; Hierro, Isabel del; Pérez, Yolanda
Abstract: The incorporation of iron and sulphate ions on TiO2 nanoparticles has been carried out in order to enhance catalytic performance in environmental remediation. The aim of this work is to design a multifunctional and visible-light active photocatalyst to remove pollutants from transportation fuels and water. The influence of doping with sulphur and iron on the physical, structural, optical, and electrochemical properties of TiO2 has been fully analyzed by a wide variety of techniques. Thus, the incorporation of a low amount of iron improves the photocatalytic performance, as in the case of 1.2%S-0.5%Fe–TiO2 photocatalyst, which shows the highest activity under visible light irradiation. The enhanced behaviour of the electron charge transfer of this photocatalyst has been confirmed by electrochemistry measurements including linear sweep voltammetry and electrochemical impedance spectroscopy. Also, the stability and recyclability of the best photocatalyst have been assessed.